Report on currency and finance 1983-84: Volume II - Bhathia, D.K. (Bombay Reserve Bank of India, 1984)
The annual data presented in this volume generally relate to financial year (April - March) except where otherwise specified
osc 01/04/2019
Ref.
Keywords: Currency question; Finance; India